2012
DOI: 10.1021/cs300558x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cage Size on the Selective Conversion of Methanol to Light Olefins

Abstract: Zeolites that contain eight-membered ring pores but different cavity geometries (LEV, CHA, and AFX structure types) are synthesized at similar Si/Al ratios and crystal sizes. These materials are tested as catalysts for the selective conversion of methanol to light olefins. At 400 °C, atmospheric pressure, and 100% conversion of methanol, the ethylene selectivity decreases as the cage size increases. Variations in the Si/Al ratio of the LEV and CHA show that the maximum selectivity occurs at Si/Al = 15−18. Beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
123
2
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(137 citation statements)
references
References 14 publications
(24 reference statements)
7
123
2
3
Order By: Relevance
“…[18] Indeed, recent descriptions have shown that AEI structures tend to produce more propylene and less ethylene than CHA catalysts, [19,20] which is interesting owing to the higher rate in the demand of propene.…”
Section: -Introductionmentioning
confidence: 99%
“…[18] Indeed, recent descriptions have shown that AEI structures tend to produce more propylene and less ethylene than CHA catalysts, [19,20] which is interesting owing to the higher rate in the demand of propene.…”
Section: -Introductionmentioning
confidence: 99%
“…Logically, for 8MR zeolites, selectivities are rather governed by the cage and window dimensions. [35][36][37] On the other hand, enhanced hydrogen transfer reactions would speed up coke formation rate. Indeed, the analysis of coking rate (Table 3) expressed as the mass of coke formed during the active period shows that rate of coke formation is almost twice higher for seeded zeolites than for hydrothermally synthesized ones (compare D-DDR 1 vs S 2 -DDR 1 and D 2 -CHA vs S 1 -CHA).…”
Section: Discussionmentioning
confidence: 99%
“…Such a prolonged lifetime of these catalysts is explained on the basis of the bigger dimensions and particular shape of the main CHA cage, which is able to accumulate more aromatics and is believed to stabilize "hydrocarbon pool" species. [35][36][37] Furthermore, there is a higher probability of blocking the 2D pore network of ZSM-58 and Sigma-1 than the 3D porosity of SSZ-13, leading to a faster deactivation of DDR. According to the literature, 38 the diamondoid species can be also formed in CHA cage however below 300 o C leading to the prompt deactivation as in case of DDR.…”
Section: Catalytic Activity In Dmtomentioning
confidence: 99%
“…This framework shows the hexagonal symmetry, the corresponding space group of symmetry is P6 3 /mmc and the unit cell idealized parameters are a = b = 13.7 Å, c = 19.7 Å. Fundamental articles on SSZ-16 present the AFX framework type in the terms of composite building units (CBU): gmelinite (gme) and aft cavities and d6r (double six-ring) cages [10,12,13], see Figure 1 (left). This method of AFX framework type representation is widely used to visualize spaces capable of accommodating sorbing species.…”
Section: Zeolite Ssz-16 and Its Structurementioning
confidence: 99%